Multi-replica provable data possession scheme supporting data dynamic updating - Long CHEN; Yu-zhu LUO (Tongxin xuebao)
Considering the application demand of multiple replicas data security and data dynamic update,a multi-replica provable data possession scheme was proposed to supporting data dynamic updating.The original data file can be dynamically updated using dynamic verification structure.The other multiple-replica data files are just append with a log-record for each dynamic update operation.The multi-replica files support public auditability and batch verification.If the original data or any replica is corrupted or missing,it can be recovered to the latest status with another copy.The performances of the communication and storage as well as the security are analyzed.The results show that the scheme is efficient and secure.